Respuesta :

Answer:

(5,6)

Step-by-step explanation:

-6x+6y=6

-6x + 3y =-12

Multiply the first equation by -1

6x-6y=-6

Add this to the second equation

6x-6y=-6

-6x + 3y =-12

---------------------

       -3y = -18

Divide each side by -3

-3y/-3 = -18/-3

y =6

Now we need to find x

6x - 6y = -6

6x -6(6) = -6

6x -36 = -6

Add 36 to each side

6x-36+36 = -6+36

6x = 30

Divide each side by 6

6x/6 = 30/6

x =5

Answer:

y= 6

x= 5

Step-by-step explanation:

i used substitution where you move everything except one variable to the the other side and substitute it into the other equation